Evaluation of Shifts in the Potential Future Distributions of Carcharhinid Sharks Under Different Climate Change Scenarios - Diaz-Carballido, Pedro Luis; Mendoza-González, Gabriela; Yañez-Arenas, Carlos Alberto; Chiappa-Carrara, Xavier (Frontiers in Marine Science, 2022)
Climate change is currently considered one of the main phenomena affecting marine species through expansion or contraction of their distribution ranges. Being ectotherm organisms, sharks of the family Carcharhinidae could be highly susceptible to the effects of climate change. They have a high ecological importance, reflected in their role in the integrity of the coastal and oceanic ecosystem as top predators that act to maintain the stability of the food chain, and economic value through fishing, consumption, and ecotourism. Currently, their populations are threatened by fishing pressure and anthropogenic activities, including meeting the demand for shark fins. Despite the ecological and economical importance of carcharhinid sharks, knowledge regarding how they are impacted by climate change is still scarce. Ecological niche modeling is a tool that allows analysis of future potential distributions under different climate change scenarios and could contribute to future planning activities and improve conservation outcomes for sharks. We generated models in Maxent in order to predict the potential geographic distribution of 25 carcharhinid sharks that inhabit Mexican waters and projected this onto future climate change scenarios (RCP2.6, RCP4.5, RCP6.0 and RCP8.5) to calculate the potential losses and gains of distribution areas. The greatest shifts in suitable areas were observed for the sharks Triaenodon obesus (gained area) and Carcharhinus porosus (lost area). Overall, under all four RCP future scenarios, six species showed gains in suitable area and 19 species showed losses. The greatest loss of suitable area for carcharhinid sharks was found with the RCP8.5 scenario; however, under this high-emissions global warming scenario, seven species actually showed an increase in distribution area. Thus, our results indicate that climate change could reduce the suitable areas for most of the species by 2050. Assessment of the distribution of shark species under climate change is urgently required in order to prioritize conservation efforts based on which species are more vulnerable, and to ensure the natural function of marine ecosystems and thus maintain the important ecosystem services they provide to human society.